Ordinary people's participation in local development planning in Nepal. Issue 2 (17th February 2022) - Bhusal, Thaneshwar; Pandeya, Ganesh Prasad
ABSTRACT: Participation of ordinary people in shaping the developmental priorities at the local level is often regarded as a vehicle to enhance the quality of local development policies, plans, and programmes. This study empirically examines a Nepali case of municipal-level development planning process to understand how ordinary people were offered participation opportunities through informal forums. Findings suggest that informal forums can be conducive for articulating the presence and voice of ordinary citizens in the local development planning process. The study contributes to the participatory development literature by showcasing a relatively successful case of incorporating ordinary people in local development planning process.